2020
DOI: 10.1152/advan.00065.2019
|View full text |Cite
|
Sign up to set email alerts
|

Learning how to learn: can embedded discussion boards help first-year students discover new learning strategies?

Abstract: Learning anatomy and physiology at university can be challenging, as students need to understand both the language of the discipline and complex topics, such as system integration. Yet learning strategies are rarely taught at university, making it difficult for students to adopt new strategies, if their approach to learning has not been effective or efficient. This study evaluated the use of small-group peer discussion boards as an avenue for sharing learning strategies between students in a first-year anatomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The students’ performances in all modules are graded on a scale of 100 at Jinan University, so it should be easier for the students to convert and report their academic performance on a scale of 10 in the survey. In relation to the correlation between students’ academic performance and the choice of online learning strategies, previous studies mainly concluded that low-performing medical students could benefit more from blended learning than high-performing students ( 32 ) and not all medical students could easily adopt a discussion based on self-directed learning strategies that might fit the online learning environment ( 33 ), especially for those low-performing students ( 34 ). This study argues that high-performing students may hold a more positive attitude toward online teaching than their low-performing counterparts in regard of instructors’ choices of teaching strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The students’ performances in all modules are graded on a scale of 100 at Jinan University, so it should be easier for the students to convert and report their academic performance on a scale of 10 in the survey. In relation to the correlation between students’ academic performance and the choice of online learning strategies, previous studies mainly concluded that low-performing medical students could benefit more from blended learning than high-performing students ( 32 ) and not all medical students could easily adopt a discussion based on self-directed learning strategies that might fit the online learning environment ( 33 ), especially for those low-performing students ( 34 ). This study argues that high-performing students may hold a more positive attitude toward online teaching than their low-performing counterparts in regard of instructors’ choices of teaching strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, blended learning paradigms incorporating AODs as an online communication tool are becoming more evident (Andresen, 2009). As blended learning becomes more prevalent, the need for a contemporary Guide will continue to increase to ensure that fit-for-purpose resources are available to support staff as they renew curriculum to accommodate current digital and pedagogical needs (Ainscough et al, 2019;Dykman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to facilitation, the design of online discussion boards is known to be important in promoting discussion as an effective and engaging learning tool (Thomas & Thorpe, 2019). Welldesigned asynchronous discussions have been found to enhance student engagement and learning (Ainscough et al, 2019;Dixson, 2010). It was encouraging to note that the design and netiquette section of the Guide was one of the most highly used.…”
Section: Discussionmentioning
confidence: 99%